LGBTQI+ safety perceptions in transit environments - Vania Ceccato; Gabriel Gliori; Catherine Sundling (Journal of Urban Mobility)
This article seeks to investigate the nature of safety perceptions of train travellers, focusing on the experiences of transgender and gender-nonconforming individuals of the environments of railway stations and the way to them. This study makes use of descriptive statistics and binary logistic regression with a dataset specially tailored from a safety survey collected in 2022 in Southern Sweden. Large variations of travellers' safety perceptions are found in relation to the time of day and across transit environments, regardless of gender or any other individual attributes or characteristics relating to their particular trips. Previous victimisation impacts safety for all groups, but travellers fear crimes that are not common in transit situations. Women are more likely to be fearful, but the most fearful of all are women who identify themselves as LGBTQI+ /other. Such a pattern is not found in men, who declare themselves to be the safest of all travellers. The implications of these results are explored both in terms of future research questions and practical implications.